3(2x-4)=0

Simple and best practice solution for 3(2x-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-4)=0 equation:


Simplifying
3(2x + -4) = 0

Reorder the terms:
3(-4 + 2x) = 0
(-4 * 3 + 2x * 3) = 0
(-12 + 6x) = 0

Solving
-12 + 6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 6x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 6x = 0 + 12
6x = 0 + 12

Combine like terms: 0 + 12 = 12
6x = 12

Divide each side by '6'.
x = 2

Simplifying
x = 2

See similar equations:

| 7y+3y=9y+9 | | 12x+34=10x+200 | | 8x-3=2x+27 | | 18w-2=10-14 | | 5x+22=x+2 | | 7(-3x+5)+8=148 | | 7t-t-8=5t-4 | | 2w+6x-14y+5w+9x+8y= | | b+12-13=(b-31) | | 3(c-2)=-15 | | -1+8(n+4)=8n+31 | | x/4+1/3=x-8 | | 2n+12=9 | | 8x+1.66666667=7x | | 2u^2-7u+6=0 | | 2r-20=-6r-2(-5r+4) | | 6w+x-4=6x+3 | | 2r-20=-6r-2(-5+4) | | 8x+8.2=12.5+7x | | 2x-1=-61 | | 4x=7x-21 | | 2x^7-32x=0 | | 7/2-8/3= | | -2(1-x)+1=5(x-2) | | 4x-16=2x+14 | | 7x+4-3x-12=8 | | 7/2+8/3= | | 61/8+3/2= | | n-5+6n=-2n+8n-13 | | 6x-2(x-6)=4(x+1)+5 | | n-5+6n=-2n+8n+31 | | x+23=-7x+5+6x |

Equations solver categories